Cadherin-7 enhances Sonic Hedgehog signalling by preventing Gli3 repressor formation during neural tube patterning - Rie Kawano; Kunimasa Ohta; Giuseppe Lupo (Open Biology, 2017)
Sonic Hedgehog (Shh) is a ventrally enriched morphogen controlling dorsoventral patterning of the neural tube. In the dorsal spinal cord, Gli3 protein bound to suppressor-of-fused (Sufu) is converted into Gli3 repressor (Gli3R), which inhibits Shh-target genes. Activation of Shh signalling prevents Gli3R formation, promoting neural tube ventralization. We show that cadherin-7 (Cdh7) expression in the intermediate spinal cord region is required to delimit the boundary between the ventral and the dorsal spinal cord. We demonstrate that Cdh7 functions as a receptor for Shh and enhances Shh signalling. Binding of Shh to Cdh7 promotes its aggregation on the cell membrane and association of Cdh7 with Gli3 and Sufu. These interactions prevent Gli3R formation and cause Gli3 protein degradation. We propose that Shh can act through Cdh7 to limit intracellular movement of Gli3 protein and production of Gli3R, thus eliciting more efficient activation of Gli-dependent signalling.